Brassinosteroids as promoters of seedling growth and antioxidant activity under heavy metal zinc stress in mung bean (Vigna radiata L.) - Kumar, Naresh; Sharma, Vikas; Kaur, Gurpreet; Lata, Charu; Dasila, Hemant; Perveen, Kahkashan; Khan, Faheema; Gupta, Vijay K.; Khanam, Mehrun Nisha (Frontiers in Microbiology, 2023)
The escalation of harmful pollutants, including heavy metals, due to industrialization and urbanization has become a global concern. To mitigate the negative impacts of heavy metal stress on germination and early plant development, growth regulators have been employed. This study aimed to evaluate the response of mung bean (Vigna radiata L.) to zinc stress in the presence of brassinosteroids, focusing on seedling growth and antioxidant potential. Mung bean seedlings were treated with three concentrations of 24-epibrassinolide (EBL) (0.1, 0.2 and 0.4 PPM) with or without zinc. Results demonstrated that the application of brassinosteroids, combined with zinc stress, significantly enhanced germination percentage (about 47.06%, 63.64% and 120%), speed of germination (about 39.13%, 50% and 100%), seedling growth (about 38% in case of treatment combined 0.4 PPM 24-EBL and 1.5 mM ZnSO4) and seedling vigor index (204% in case of treatment combined 0.4 PPM 24-EBL and 1.5 mM ZnSO4) compared to zinc-treated seedlings alone after 24 Hrs. The activities of antioxidative enzymes (catalase, ascorbate peroxidase, polyphenol oxidase and peroxidase) and total soluble protein content decreased, while lipid peroxidation and proline content exhibited a significant increase (P≤0.05) when compared to the control. However, the negative effects induced by heavy metal stress on these parameters were significantly mitigated by EBL application. Notably, the most effective concentration of EBL in overcoming zinc stress was found to be 0.4 PPM. These findings underscore the potential of exogenously applied brassinosteroids as a valuable tool in phytoremediation projects by ameliorating heavy metal stress.